Facile Synthesis of Ag@Pt Core‐Shell Nanoparticles with Different Dendrites Pt Shells. Issue 29 (12th October 2017) - Wu, Haofei; Qi, Weihong; Peng, Hongcheng; He, Jieting
Abstract: We presented a simple method for synthesis of various Ag@Pt nanoarchitectures via overgrowth of Pt shell structures in Ag cores by controlling the amount of Pt precursor. When the molar ratio of Ag‐to‐Pt precursor was 1: 3 and 1: 4, the Ag@Pt3 and Ag@Pt4 nanoparticles had a large number of Pt branches, which lead to a large electrochemically active specific surface area (45.5 m 2 /gPt, 59.05 m 2 /gPt, respectively). And compared with commercial Pt/C (323.9 mA/mgPt ), Ag@Pt3 (381.1 mA.mgPt )and Ag@Pt4 (479.2 mA/mgPt ) had a better catalytic effect inthe methanol oxidation reaction (MOR). Abstract : We presented a simple method for synthesis of various Ag@Pt nanoarchitectures via overgrowth of Pt shell structures in Ag cores by controlling the amount of Pt precursor, while the electrocatalytic performance of the particles depends on their composition and morphology.